Neuroprotective Properties of Omega-3 in Ischemic Cerebrovascular Accident: A Systematic Review / Propriedades Neuroprotetoras do Ômega-3 no Acidente Vascular Cerebral Isquêmico: Uma Revisão Sistemática - Feitosa, Pedro Walisson Gomes (2022)
Abstract: Cerebrovascular Accident (CVA) is a neurological disorder whose pathophysiology of ischemic side occurs together with the development of a central inflammatory process. Thus, omega-3 fatty acids appear as a potential agent in the prevention and treatment of the repercussions of this ischemic event. This work aims to develop a systematic review of the literature on the neuroprotective potential of omega-3 in terms of preventive and therapeutic aspects in ischemic stroke. A bibliographic review was carried out in the PubMed and Scopus electronic databases, and 12 indexed articles were included in the final sample and applied for discussion. Studies have pointed to the decrease in omega-3 as harmful to nerve tissue regeneration, as well as the neuroprotective role of omega-3 in cerebral ischemia after ischemia-reperfusion injury in animal models. Reduction of cerebral edema, promotion of angiogenesis, preservation of the integrity of the blood-brain barrier and tissue protection were also observed.Keywords : Cerebral ischemia. Omega-3 Polyunsaturated Fatty Acids. Neuroprotection. Resumo: O Acidente Vascular Encefálico (AVE) é um distúrbio neurológico cuja fisiopatologia do lado isquêmico ocorre juntamente com o desenvolvimento de um processo inflamatório central. Dessa forma, os ácidos graxos ômega-3 aparecem como potencial agente na prevenção e tratamento das repercussões desse evento isquêmico. Este trabalho tem como objetivo desenvolver uma revisão sistemática da literatura sobre o potencial neuroprotetor do ômega-3 quanto aos aspectos preventivos e terapêuticos no AVC isquêmico. Foi realizada uma revisão bibliográfica nas bases de dados eletrônicas PubMed e Scopus sendo que 12 artigos indexados foram incluídos na amostra final e aplicados para discussão. Os estudos apontaram a diminuição do ômega-3 como prejudicial à regeneração dos tecidos nervosos, bem como o papel neuroprotetor do ômega-3 na isquemia cerebral após lesão de isquemia-reperfusão em modelos animais. Também foram observadas redução do edema cerebral, promoção da angiogênese, preservação da integridade da barreira hematoencefálica e proteção tecidual.Palavras-chave: Isquemia cerebral. Ácidos graxos poliinsaturados ômega-3. Neuroproteção.